Phylogenetic relationships between Palaearctic species of the Anopheles maculipennis complex (Diptera: Culicidae) revealed by different approaches and markers. The problem of consensus - O. V. Vaulin; Yu. M. Novikov (Вавиловский журнал генетики и селекции)
A study of phylogenetic relationships in closely related groups of epidemically important species is an important task of parasitology and evolutionary theory. One of these species groups is the maculipennis complex, with its members widespread in Eurasia, North Africa and North America. We studied phylogenetic schemes of the Palaearctic part of this Complex, which are based on crossability of species, polytene chromosomes, isoenzymes, cuticular hydrocarbons and ITS2 of rRNA genes. The lack of high compliance between them prompted us to create a consensus scheme of phylogenetic relationships in the Palaearctic part of this Complex. We constructed phylogenetic schemes on the sequences of a COI gene fragment, the D2 variable region of 28S rDNA and ITS2 of rRNA genes using various algorithms (Neighborjoining, Minimum Evolution, Maximum parsimony and Maximum likelihood). Two consensus schemes of the Palaearctic branch of the maculipennis complex were constructed, validated and discussed. The first scheme was based mostly on molecular genetics data. The second scheme relies on polytene chromosome, geographical spread and ecological data. Phylogenetic relationships of An. beklemishevi are contradictory. This species is similar to other Palaearctic species by molecular markers but it is far from them by fixed chromosome inversions. It was shown that this species is distant from Neoarctic species of the An. quadrimaculatus branch. The proposed schemes show two possible scenarios of the maculipennis complex evolution. Differences between them are explained by facts and associated speculations as well as by assumptions made under different phylogenetic reconstruction methods. A hypothesis about a significant role of the disparity between the astronomical and biological times in the interpretation of evolutionary processes was proposed. To address the phylogeny problem of the Palaearctic branch of the maculipennis complex at a more detailed level, it is required to increase our knowledge about the underlying species.